Genetic and Environmental Factors in Invasive Cervical Cancer: Design and Methods of a Classical Twin Study. (5th December 2016) - Machalek, Dorothy A.; Wark, John D.; Tabrizi, Sepehr N.; Hopper, John L.; Bui, Minh; Dite, Gillian S.; Cornall, Alyssa M.; Pitts, Marian; Gertig, Dorota; Erbas, Bircan; Garland, Suzanne M.
Abstract : Background: Persistent high-risk human papillomavirus (HPV) infection is a necessary prerequisite for development of cervical cancer and its precursor lesion, high-grade squamous intraepithelial lesion (HSIL). However, HPV infection is not sufficient to drive this process, and genetic and environmental factors may also play a role. Methods/Design: The Cervical Cancer, Genetics and Environment Twin Study was established to investigate the environmental and genetic influences on variation in susceptibility to cervical pre-cancer in 25- to 69-year-old monozygotic (MZ) and dizygotic (DZ) twins recruited through the Australian Twin Registry. Reviews of Papanicolaou (Pap) screening histories were undertaken to identify individual women with a history of an abnormal Pap test. This was followed by detection of HPV in archival Pap smears of selected twin pairs to determine HPV persistence. Selected twin pairs also completed a detailed questionnaire on socio-demographic characteristics, sexual behavior, and HPV knowledge. In future analyses, under the assumptions of the classical twin design, case-wise concordance for persistent HPV infection and HSIL will be calculated for MZ and DZ twin pairs, and twin pairs (both MZ and DZ) who are discordant for the above outcomes will be used to assess the contributions of measured environmental risk factors. Discussion: The study examines factors related to HPV persistence and development of HSIL among female MZ and DZ twins. The results will contribute to our understanding of the natural history of cervical HPV infection and the relative contributions of genetic and environmental factors in disease progression.